Penerapan Media Gambar Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas III SD Negeri 050726 Tanjung Pura - Aprianty; Lailatun Nur Kamaliah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This research aims to improve mathematics learning outcomes for class III students at SD N 9 Subagan through the application of image media. This research is classroom action research carried out in two cycles consisting of planning, implementation, observation, evaluation and reflection stages carried out in each cycle. The subjects of this research were 15 class III students in the second semester of the 2022/2023 academic year. The results of the research show that student learning outcomes in Mathematics, especially the material on calculating the number of folded symmetries and rotational symmetries in flat shapes by applying picture learning media in class III of SD Negeri 050726 Tanjung Pura, can be said to be successful. This can be seen based on the results of the post-test in cycle I and cycle II, namely: out of 15 students, based on the results of the post-test in cycle I it can be seen that 10 students or 67% were declared to have completed their studies, while 5 students or 33 % were declared still incomplete in learning and in cycle II it was found that 14 students or 93% were declared complete in learning, while 1 student or 7% were declared still incomplete in learning. Thus, the application of image learning media in class III at SD Negeri 050726 Tanjung Pura can improve student learning outcomes, as evidenced by the change in learning outcomes increasing by 27% from cycle I to cycle II for class III students at SD N 9 Subagan. Keywords: Image Media; Learning outcomes.